Local Drug Delivery Agents As Adjunct To Conventional Therapy For Furcation Defects: A Systematic Review And Meta-Analysis (Bangladesh Journal of Medical Science, 2025)
Background Dental plaque is the etiologic factor for various periodontal problems. It is a chronic inflammatory disease initiated by dental plaque. Chronic periodontitis affects the root trunk of multirooted teeth. Pharmacologic management is used as an adjunct to conventional scaling and root planing (SRP). It includes chlorhexidine mouth rinses, subgingival irrigation and local drug delivery (LDD) agents. Potential therapeutic agents such as non-steroidal anti‑inflammatory drugs, chemically modified tetracyclines and bisphosphonates to treat bone resorption are well documented in literature. However, the use of LDD agents needs further exploration. To determine the efficacy of LDD agents as an adjunct to SRP for treating furcation defects in chronic periodontitis.Materials and Methods Protocol was registered in prospero, no: CRD42019145936. Databases searched were PUBMED, COCHRANE, up to March 2019, without language restrictions. Studies in trial registers, handsearching, bibliographic references of relevant articles were also checked. Data collection and analysis was done by individual authors. Three review authors independently assessed studies for eligibility. Three review authors then extracted data and assessed the risk of bias for individual studies using standard Cochrane methodology. We assessed the evidence using GRADE and created ’Summary of findings’ tables.Results Meta-analysis was done including five studies (Pradeep2012, Pradeep 2013, Gupta2019, Singhal2017, Garg2016,) It supported that local drug delivery as an adjunct to scaling and root planing is more effective than scaling and root planing alone. We included five studies reporting data from 390 participants, aged 18+ years, comparing local drug delivery agents plus “scaling and root planing” with “scaling and root planing” with placebo. Studies reported data on periodontal parameters like pocket depth, gingival bleeding, clinical attachment loss. Indices including plaque index and gingival index. Ipshita2018 used and compared both allopathic and herbal agent hence was not included for meta-analysis. Due to the differences in the time of reporting of the included studies, all of them were not included for meta-analysis. Meta-analysis was done including five studies (Pradeep2012, Pradeep 2013, Gupta2019, Singhal2017, Garg2016,) It supported that the use of local drug delivery as an adjunct to scaling and root planing is more effective than scaling and root planing alone.Conclusion Use of LDD agents as adjunct to SRP is more effective in treating furcation defects.Bangladesh Journal of Medical Science Vol. 24 No. 01 January’25 Page : 293-308